Current Perspectives in the Discovery of Newer Medications Against the Outbreak of COVID-19 - Ramesh, M.; Anand, Krishnan; Shahbaaz, Mohd; Abdellattif, Magda H. (Frontiers in Molecular Biosciences, 2021)
A rapid and increasing spread of COVID-19 pandemic disease has been perceived worldwide in 2020. The current COVID-19 disease outbreak is due to the spread of SARS-CoV-2. SARS-CoV-2 is a new strain of coronavirus that has spike protein on the envelope. The spike protein of the virus binds with the ACE-2 receptor of the human lungs surface for entering into the host. Therefore, the blocking of viral entry into the host by targeting the spike protein has been suggested to be a valid strategy to treat COVID-19. The patients of COVID-19 were found to be asymptomatic, cold, mild to severe respiratory illness, and leading to death. The severe illness has been noted mainly in old age people, cardiovascular disease patients, and respiratory disease patients. However, the long-term health effects due to COVID-19 are not yet known. Recently, the vaccines were authorized to protect from COVID-19. However, the researchers have put an effort to discover suitable targets and newer medications in the form of small molecules or peptides, based on in-silico methods and synthetic approaches. This manuscript describes the current perspectives of the causative agent, diagnostic procedure, therapeutic targets, treatment, clinical trials, and development of potential clinical candidates of COVID-19. The study will be useful to identify the potential newer medications for the treatment of COVID-19.